PENGARUH KUALITAS PRODUK, CITRA MEREK DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi Kasus pada Mahasiswa Pengguna Smartphone Samsung di Universitas Stikubank Semarang) - Aisyah Sarania, 15.05.51.0064; Kasmari, Kasmari (Students' Journal of Economic and Management, 2019)
This study aims to test and analyze the effect of product quality, brand image, and brand awareness on Samsung smartphone purchasing decisions. The population in this study were students of Samsung smartphone users at Stikubank University Semarang, this study took a sample of 99 respondents. The sampling technique in this study used proportionate random sampling. The data used in this study is primary data, with a questionnaire as a research instrument. The analytical tool used is validity test, reliability test, multiple linear regression, F test, coefficient of determination test (R²), and t test (hypothesis), which is then processed by calculation of SPSS (Statistical Product and Solutions) version 22. The results showed that product quality had a positive and significant effect on purchasing decisions, brand image had a positive and significant effect on purchasing decisions, and brand awareness had no effect and significant effect on purchasing decisions